New accents in language education: changes in the “Common European Framework of References for Languages: Learning, Teaching, Assessment. Companion Volume with New Descriptors” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
In the article are analyzed the changes and additions to the “European Recommendations on Language Education”, which were adopted in 2018. Among the reasons that prompted the revision of the Common European Framework of References for Languages: Learning, Teaching, Assessment (2000) are the transformations in the social sphere, technical progress and informatization of society. Among the challenges posed by migration and globalization is the emergence of multilingual societies, which has prompted the search for new language teaching methods. Among them is the didactics of multilingualism, the elements of which are taken into account in the Companion Volume. Attention is drawn to the appearance in the new edition of descriptors to previously only indirectly named communicative actions, which were not described in the skills (mediation), the inclusion of online communication as a type of speech activity, adding pre-A 1 level, as well as levels A 2+, B 1+, B 2+ to the already existing ones, which will allow to determine the level of language proficiency more differently. Progression in the description of skills of different levels is shown on the examples of descriptors of mediation and online-communication. The changes also affect intercultural competence, the level of development of which is taken into account in all types of speech activities. It is emphasized that the new accents in the Companion Volume will update the content of language training and improve its quality, but they are also a challenge for the system of language education and methods of language teaching.
Keywords: language education; methods of language teaching; didactics of multilingualism; mediation; intercultural competence